2021
DOI: 10.1002/eco.2382
|View full text |Cite
|
Sign up to set email alerts
|

Transpiration patterns and water use strategies of beech and oak trees along a hillslope

Abstract: The role of landscape topography in mediating subsurface water availability and ultimately tree transpiration is still poorly understood. To assess how hillslope position affects tree water use, we coupled sap velocity with xylem isotope measurements in a temperate beech-oak forest along a hillslope transect in Luxembourg. We generally observed greater sap velocities at the upslope locations in trees from average-sized trees, suggesting the presence of more suited growing conditions. We found a lower differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
41
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 110 publications
8
41
0
1
Order By: Relevance
“…Additionally, during the dormant season, δ 18 O and δ 2 H showed the heaviest values of the studied period (Figures 2 and 3). The occurrence of the heavy isotopic composition in xylem water during leafless periods was previously reported in other studies (Martín-G omez et al, 2017;Oerter et al, 2019;Phillips & Ehleringer, 1995) and also observed in the study area in 2019 (Fabiani et al, 2021). This observation has been explained by the evaporation through the bark that occurs over the dormant season when sap flow is ceased (Martín-G omez et al, 2017;Oerter et al, 2019;Phillips & Ehleringer, 1995).…”
Section: Xylem Depth-related Variability Of Isotopic Composition In B...supporting
confidence: 85%
“…Additionally, during the dormant season, δ 18 O and δ 2 H showed the heaviest values of the studied period (Figures 2 and 3). The occurrence of the heavy isotopic composition in xylem water during leafless periods was previously reported in other studies (Martín-G omez et al, 2017;Oerter et al, 2019;Phillips & Ehleringer, 1995) and also observed in the study area in 2019 (Fabiani et al, 2021). This observation has been explained by the evaporation through the bark that occurs over the dormant season when sap flow is ceased (Martín-G omez et al, 2017;Oerter et al, 2019;Phillips & Ehleringer, 1995).…”
Section: Xylem Depth-related Variability Of Isotopic Composition In B...supporting
confidence: 85%
“…Fan et al [61] describe an average rooting depth of 5.23 m for oak and 0.8 m for beech. With such a distributed root system, beech mainly utilised the near-surface soil water, i.e., the effective precipitation, as is described by Fabiani et al [32]. On the other hand, oak could use the effective precipitation and, also, the groundwater, which its deep roots were able to reach [62].…”
Section: Discussionmentioning
confidence: 97%
“…Stands of European beech and sessile oak exhibit different patterns of transpiration due to their root system type, stomatal regulation in response to environmental variables, leaf area index or forest management [30,31]. A recent study indicated that oak in the mixed forest transpired more water than beech, especially in the dry periods [32]. It was most likely due to different rooting patterns.…”
Section: Introductionmentioning
confidence: 99%
“…7) also suggested that the transient storage at our site became less important in controlling solute transport with increasing discharge. The decrease in A TS and T sto with the increasing discharge has been argued to indicate an increase in groundwater gradients toward the stream channel with a consequent decrease in the hyporheic zone at different study sites (Morrice et al, 1997;Fabian et al, 2011). However, the observed groundwater gradients at the study site exclude the presence of significant hyporheic exchange during the three simulated tracer experiments.…”
Section: Implications Of Identifiable Model Parameters For Hydrologic...mentioning
confidence: 89%
“…The studied stream reach (49 • 49 38 N, 5 • 47 44 E) is located in western Luxembourg, downstream of the Weierbach experimental catchment (Hissler et al, 2021;Fabiani et al, 2022). The stream channel is unvegetated with a slope of 6 % and consists of deposited colluvium material and fragmented schists (up to 50 cm depth) with local outcrops of fractured slate bedrock in the streambed.…”
Section: Study Site and Tracer Datamentioning
confidence: 99%